Speckle reduction in laser projection based on a rotating ball lens. (March 2021) - Deng, Linxiao; Dong, Tianhao; Fang, Yuwei; Yang, Yuhua; Gu, Chun; Ming, Hai; Xu, Lixin
Highlights: Efficient no-diffuser speckle reduction based on rotating ball lens with light pipe. Achieved less light loss and more uniform image brightness. Standardised speckle measurement method replicating human eye functions. Development of a measurement system using a charge-coupled device camera. Low-cost and easily fabricated system for accurate and rapid measurements. Abstract: A speckle reduction method based on a rotating ball lens is proposed and assessed. The fast rotation of the ball lens results in angle diversity and thus reduced speckle. Furthermore, the same experiment is performed with different motor voltages, shooting distances, and laser driving currents. Efficient speckle reduction was achieved by applying our method to a complete laser projection system, resulting in a lower speckle contrast than the human speckle perception threshold of 4%. Additionally, a novel standardised speckle measurement method based on human eye characteristics was developed to evaluate the speckle contrast. The proposed method can increase opportunities for practical speckle measurement applications.